Multifocal Primary Non- Hodgkin’s Lymphoma of the Oral Cavity: Report of Three Cases and Review of the Literature - Atarbashi Moghadam, Saedeh; Lotfi, Ali; Moshref, Mohammad (Journal of Dental School, 2019)
Objective: Oral non- Hodgkin’s lymphoma (NHL) is a relatively rare neoplasm that may develop in the soft tissues or jaw bones, with or without node or marrow involvement. Oral lymphomas are often difficult to diagnose as there are no characteristic clinical features and usually appear as non- tender swellings. Case: We describe clinical, radiographic, histopathological and immunohistochemical findings of three cases of multifocal NHLs presenting in the oral cavity. Conclusion: If the oral lesion is multifocal, extra nodal lymphoma must be considered in the differential diagnosis.